Analisis Persepsi Pelayanan Kapal Malam Rute Kendari - Raha Provinsi Sulawesi Tenggara - Saputra, Muhammad Roni Anwar; Lakawa, Irwan; Huiyanto, Hujiyanto; Jassin, Andi Makkawaru; Sufrianto, Sufrianto (Universitas Sulawesi Tenggara, 2022)
The characteristics of night ship passengers are dominated by men, the average age of passengers is 20-25 years with a percentage value of 64%, the most travel destinations are Muna Island and the dominant service users have student jobs, while the analysis results are seen in the value of 0.66- 0.8, this means that the overall CSI score for performance appraisal is 1.96 with the criteria for the value of each indicator, service users are very satisfied with the performance of night ship services on the Kendari - Raha route, Southeast Sulawesi Province. The perception of service users towards night boat services on the Kendari - Raha route as a whole with an average value of 3.5 for performance and 3.1 for satisfaction. This can be seen in the quadrant A diagram in the Cartesian diagram, which means that the service elements are very good and provided very well.